Implementasi Gadai Masyarakat Kabupaten Aceh Tenggara Perspektif Tokoh Agama dan Tokoh Masyarakat - Iis Janisa (JES (Jurnal Ekonomi Syariah), 2026)
Pawning (rahn) is an Islamic debt collateral transaction (muamalah) to ensure repayment of a qardh (debt) agreement. Traditional practices, such as pawning rice fields, are common but often contradict Islamic muamalah concepts, leading to ribawi or gharar transactions. This study analyzed the compatibility of rice field pawning practices in Southeast Aceh with Islamic law, based on the perspectives of religious and community leaders. The qualitative, inductive analysis found that local pawning practices are generally not compliant with Islamic law, mainly due to the community's lack of knowledge regarding the technicalities and contracts of rahn. To eliminate gharar, a collaborative effort from the government, religious, and community leaders is necessary. Rice fields and gardens are the typical collateral due to the region's dependence on agriculture.